Personalized Learning As a Psychological Learning Solution for Student Disabilities When Social Distances COVID-19 - Rinalfi Rinalfi; Neviyarni Suhaili (Pedulidisabilitas Center, 2021)
Since development of information and communication technology, there have been many claims from learning technologists that role of educators will diminish and even end, but these claims have so far not been proven even though multimedia technology is increasingly sophisticated, where learning with the help of computer-based interactive media makes it possible for learners to carry out learning activities without help from others. In addition, learning models also provide support for increasingly individualized forms of learning, one of which is personilized learning, which gives every learner the opportunity to progress according to their respective speed and abilities. Psychology learning can be accessed anywhere and mastery of the material as desired without being constrained by the development of other students. Thus, the combination of sophistication of interactive multimedia technology and individual learning models reinforces the assumption that role of educators will end in future, therefore this paper examines whether these concerns are theoretically relevant.